Analysis of Morocco's renewable energy production and transmission potential - Vaida Zemlickienė; Boumediene Amraoui; Najiba El Amrani El Idrissi (Insights into Regional Development)
Alongside efforts to reduce carbon emissions, energy production and use took on new urgency last year, when Europe and other countries faced harsh realities regarding electricity availability and affordability; therefore, solutions are needed to avoid the consequences of the existing gas monopoly because electricity prices are directly correlated with gas prices. One possible alternative to solving this problem is to purchase sustainable electricity from countries with high potential to produce and sell electricity from renewable sources, such as Morocco. A detailed examination of the current situation and the mentioned potential above is required to find new solutions that can have significant political consequences. Publicly available secondary information and scientific literature were investigated to reflect the current situation; statistical information was collected and analyzed to find out the cases of energy transfer from Morocco to other countries; expert investigation was carried out to identify the specifics of problems related to renewable energy production and transmission to Europe. Actual cases of electricity transmission have been or are currently happening only between neighbouring countries Spain and Algeria. The electricity transmission with Algeria is interrupted due to political disagreements. Three future electricity transmission connections are planned: a substantial long-distance project - "Xlinks" with the UK; second, with Portugal, and discussions are underway regarding Mauritania. Morocco can become an essential actor by exporting electricity to Europe, considering its proximity to Spain and huge potential for solar and wind energy that can fulfil the needs of all of Europe. However, it is essential to pay attention; not only Europe but African countries are on the list of those who want to purchase Moroccan electricity.